ESL Students’ Constraints and Strategies in Performing Sight Translation - Fauzia, Maya Rizki (English Department, Universitas Negeri Surabaya, 2022)
Sight translation is a combination of the elements of translation and interpretation in which interpreters read source language text silently and render information to target language out loud. It has been considered as supportive teaching methods for interpreting training. Sight translation takes place during medical consultation, in the court, conference, and meetings. Simultaneous Interpreting is one of the compulsory courses at D4 English for Tourism Industry Politeknik Negeri Malang. Sight translation is discussed and practiced in the class as an attempt to prepare students for simultaneous interpreting. Instructional texts from various fields are used as learning materials in the class. Objective of this study is to identify problems students encountered while performing sight translation and explain some strategies they applied. 38 audio recordings, where students were asked to conduct sight translation of tourism-related text from English to Indonesia, were analyzed in this descriptive-qualitative study. The recordings were transcribed and analyzed to gain information on students’ constraints and strategies in sight translation. As an addition, questionnaires were distributed to probe data related students’ problems in sight translation. The findings showed that lack of vocabulary which led to inaccurate translation and inaccurate word choice became the major hindrance in performing sight translation. Furthermore, transcribing, deletion, borrowing, addition and use of hypernym are the strategies the majority of the students utilized as an attempt to complete their sight translation. Transcribing or word-per-word translation prevented students from conveying accurate messages into the target language.